The return from underperformance to sustainable world-class level: A case study of a male cross-country skier - Talsnes, Rune Kjøsen; Moxnes, Einar Flaktveit; Nystad, Trond; Sandbakk, Øyvind (Frontiers in Physiology, 2023)
Abstract Purpose: To determine the main factors associated with unexpected underperformance and prospectively describe the holistic process of returning to sustainable world-class level in a male cross-country skier. Methods: Longitudinal training data was retrospectively analyzed across nine seasons (2012-2013 to 2020-2021), and categorized into training forms (endurance, strength, and speed), intensities (low- [LIT], moderate- [MIT], and high-intensity training [HIT]), and modes (specific and non-specific). Performance data was obtained from the International Ski and Snowboard Federation (FIS). Following two seasons of unexpected underperformance (2019-2020 and 2020-2021), the participant was prospectively followed in the process of returning to sustainable world-class level (2021-2022). Day-to-day training data and physiological tests were analyzed, and interviews with the participant and the head coach conducted. Results: Longitudinal training data from 2012-2013 to 2018-2019 demonstrated a non-linear 30% increase in total training volume (from 772 h to 1002 h), mainly caused by increased volume of ski-specific endurance training without changes in intensity distribution. Coincidingly, the participant gradually reached a world-class performance level. After two seasons of unexpected underperformance with relatively similar training volumes and intensity distributions as in the preceding seasons, the possible contributing factors were identified: lack of training periodization, limited monitoring and intensity control, particularly in connection with a “extreme” regime of training with low carbohydrate availability and days including two MIT sessions, as well as lack of systematic technique training and follow-up by coaches on a daily basis. Consequently, the return to world-class level included the introduction of a clear micro-cycle periodization, more systematic physiological monitoring and testing, more accurate intensity control, increased carbohydrate intake during and between sessions, as well as increased emphasize on technique training and an assistant coach present during day-to-day training. Conclusions: These longitudinal data describe the main factors leading to unexpected underperformance, in addition to providing unique insights into the corresponding process of returning to sustainable world-class level in a male cross-country skier. The holistic approach described in this case study may serve as a theoretical framework for future studies and practical work with underperforming endurance athletes.